Mechanisms of exchange : transmission in medieval art and architecture of the Mediterranean, ca. 1000-1500 - Grossman, Heather E.; Walker, Alicia (Brill, 2013)
"Featuring eight innovative studies by prominent scholars of medieval art and architecture, this special issue of Medieval Encounters examines the specific means by which art and architectural forms, techniques, and ideas were transmitted throughout the medieval world (ca. 1000-1500). While focusing on the Mediterranean region, the collection also includes essays that expand this geographic zone into a cultural and artistic one by demonstrating contact with near and distant neighbors, thereby allowing an expanded understanding of the interconnectedness of the medieval world. The studies are united by a focus on the specific mechanisms that enabled artistic and architectural interaction, as well as the individuals who facilitated these transmissions. Authors also consider the effects and collaboration of portable and monumental arts in the creation of intercultural artistic traditions"--Back cover